PENGARUH BAKAT DAN KREATIVITAS TERHADAP JIWA KEWIRAUSAHAAN NASABAH KOPERASI ANUGRAH MEGA MANDIRI CABANG JATIMAKMUR - Lailia Istiqomah; Amanda Setiorini (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
The purpose of this study was to determine the effect of talent and creativity on the entrepreneurial spirit of the customers of the Jatimakmur branch of the Anugrah Mega Mandiri Cooperative. Data collection uses a questionnaire, and the method of analysis uses simultaneously and partially linear regression. The results showed that talent has a significant effect on the entrepreneurial spirit, creativity also has a significant effect on the entrepreneurial spirit. Simultaneously, talent and creativity show significant results for the entrepreneurial spirit of the customers of the Jatimakmur branch of the Anugrah Mega Mandiri Cooperative.